Keabsahan Kontrak Elektronik (E-Contract) dalam Transaksi E-Commerce berdasarkan Undang-Undang Nomor 11 Tahun 2008 tentang Informasi dan Transaksi Elektronik - Anggraini, Sherlyna Resti; Amini, Aisyah; Nugroho, Lucky Dafira (Lembaga Yasin AlSys, 2025)
This study aims to examine and analyze the legal validity of electronic contracts in e-commerce transactions in Indonesia, with a focus on the legal provisions stipulated in Law Number 11 of 2008 concerning Electronic Information and Transactions (UU ITE). A normative juridical method was employed to address the issue of electronic contract validity, which remains a primary challenge amid the rapid advancement of technology and the digitalization of transactions. A key factor influencing this validity is the public’s limited understanding of the legal aspects of digital contracts. In today’s digital era, e-commerce transactions have become increasingly dominant, with electronic contracts serving as the principal instruments in conducting online business activities. This study analyzes essential aspects of the legality of electronic contracts, including consent and electronic signatures, party identification, consumer protection, and dispute resolution mechanisms. The findings reveal that although the UU ITE provides a strong legal foundation, there is a continued need for legal education, regulatory refinement, and the strengthening of dispute resolution systems to ensure the lawful and effective implementation of electronic contracts. The study underscores the importance of compliance with legal requirements in digital transactions and the role of the UU ITE in safeguarding the legality and credibility of Indonesia’s e-commerce system. The implications support the reinforcement of the national legal framework to promote sustainable and trustworthy growth in digital transactions.